Meningkatkan Motivasi Belajar Siswa dengan Menggunakan Metode Kerja Kelompok pada Mata Pelajaran Pendidikan Agama Kristen di SMP Negeri I Totikum Sulawesi Tengah - Jafarhari Papasi (Universitas Pendidikan Mandalika, 2020)
This study aims to increase student learning motivation by using group work methods in Christian religious education subjects. This research method uses classroom action research. Subjects in this study were 18 grade students of SMP Negeri I Totikum. The research instrument used tests and observations. While the data analysis technique used qualitative and quantitative descriptive analysis. The results of this study indicate that the learning process using work methods can increase student motivation so that it has a positive impact on the final grades obtained by students. Based on the results of observations in cycle I and cycle II through observing student activity in the learning process and student learning outcomes, it was obtained data that all students liked the way of learning and were motivated to learn using the group work method on the grounds that the learning process was fun and did not make it saturated.